2022
DOI: 10.3390/toxics10120744
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Comprehensive Review on Arsenic-Induced Male Reproductive Toxicity and Mechanisms of Phytonutrient Intervention

Abstract: Arsenic (As) is a poisonous metalloid that is toxic to both humans and animals. Drinking water contamination has been linked to the development of cancer (skin, lung, urinary bladder, and liver), as well as other disorders such as diabetes and cardiovascular, gastrointestinal, neurological, and developmental damage. According to epidemiological studies, As contributes to male infertility, sexual dysfunction, poor sperm quality, and developmental consequences such as low birth weight, spontaneous abortion, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 201 publications
1
4
0
Order By: Relevance
“…The study showed that arsenic trioxide depleted sperm morphology following its ingestion, which is linked to lipid peroxidation and ROS generation suppressing the hypothalamic Gonadal axis function (88)(89)(90) acting through the AKT signalling pathway. The study is in line with (56,(58)(59)(60)(91)(92)(93)(94), indicating a significant increase in abnormal sperm cells and significant decline in normal sperm cells. However, treatments with MET and ELAM in the ameliorative and protective phase improve sperm morphology.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The study showed that arsenic trioxide depleted sperm morphology following its ingestion, which is linked to lipid peroxidation and ROS generation suppressing the hypothalamic Gonadal axis function (88)(89)(90) acting through the AKT signalling pathway. The study is in line with (56,(58)(59)(60)(91)(92)(93)(94), indicating a significant increase in abnormal sperm cells and significant decline in normal sperm cells. However, treatments with MET and ELAM in the ameliorative and protective phase improve sperm morphology.…”
Section: Discussionsupporting
confidence: 81%
“…Exposure to arsenic forms results in biological dysfunction processes that have resulted in cardiovascular diseases, diabetes, neurocognitive outcomes, and reproductive dysfunction (2,3) linked to oxidative stress. Arsenic-associated male infertility is caused by oxidative stress, which results to altered hormonal profiles, increased oxidative stress, DNA damage, and metabolic issues connected to spermatogenesis and steroidogeneses (4), which acts through the activation of the ERK/AKT/NF-kβ pathway been the primary molecular mechanisms in male infertility following arsenic trioxide exposure (5,6). Its exposure to humans is through drinking water, highly industrialized activities, cosmetics, smoking, and other air sources (7).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most recognized comprise glutathione-dependent reduction reactions of pentavalent methylated arsenic species, monomethylarsenate V and dimethylarsenate V [ 17 , 44 , 45 ]. Arsenic is known for its high toxicity and carcinogenicity, raising the risk for bladder, lung, kidney, and liver cancer development [ 46 ]. Unfortunately, the environmental and occupational exposure to aforementioned arsenic compounds in the association with glutathione S-transferase O1 and O2 polymorphisms could not be assessed in this pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…Cd [ 5 ] and As [ 6 ] can disrupt the repair function of DNA damage, leading to genetic mutations and various cancers. Exposure to As may alter the hypothalamic-pituitary-gonadal (HPG) axis, decreasing testosterone synthesis and spermatogenesis [ 7 ]. As a nutritional antioxidant, zinc is crucial in maintaining various cellular pathways.…”
Section: Introductionmentioning
confidence: 99%